Clostridium ventriculi bacteremia following acute colonic pseudo-obstruction: A case report. (October 2019) - Bortolotti, Perrine; Kipnis, Eric; Faure, Emmanuel; Faure, Karine; Wacrenier, Agnès; Fauquembergue, Maud; Penven, Malo; Messaadi, Sophian; Marceau, Laure; Dessein, Rodrigue; Le Guern, Rémi
Abstract: Clostridium ventriculi (formerly Sarcina ventriculi ) is a Gram-positive, obligate anaerobic coccus. Human infections due to this bacterium have rarely been reported, its involvement in the development of gastric ulcers and perforation has been suggested. We present a case of bacteremia due to C. ventriculi following acute colonic pseudo-obstruction. Highlights: Acute colonic pseudo-obstruction can lead to bacterial translocation with anaerobes. We describe Clostridium ventriculi bacteremia following colonic pseudo-obstruction. C. ventriculi are large anaerobic Gram-positive cocci in clusters of tetrads. Treatment with piperacillin/tazobactam for 10 days was successful.